Deep crustal refraction and reflection seismics. Crustal and sedimentary structures and geodynamic evolution of the West Antarctic continental margin and Pine Island - Gohl, Karsten; Lemenkova, Polina; Grobys, J.; Parsiegla, N.; Netzeband, Gesa; Uenzelmann-Neben, G.; Schlüter, Philipp; Lensch, Norbert; Bohlmann, Harald; Fahl, A.; Eagles, Graeme; Feigl, Thomas; et al. (2006)
Accurate models of the geodynamic-tectonic evolution contain some of the most important parameters for understanding and reconstruction of the palaeo- environment. Geophysical surveys of the sedimentary sequences and the underlying basement of the shelf and slope of the southern Amundsen Sea, Pine Island Bay and its adjacent continental rise allow reconstructions of the formation of the tectonic and older sedimentary processes. The following objectives are addressed as part of a cooperative project between the Vernadsky Institute in Moscow (Dr. Gleb Udintsev) and AWI:• Identification of the boundaries between suspected crustal blocks and volcanic zones in Pine Island Bay. The glacier troughs and Pine Island Bay are thought to have developed along such tectonic boundaries.• During and after separation from the Chatham Rise and Campbell Plateau (New Zealand), the continental margin of Marie Byrd Land developed as a passive margin, probably accompanied by intensive volcanism. The question is whether this volcanism occurred mainly during the rifting process or during post-rift phases, or if it developed in relation to the West Antarctic rift system.• Recording of the sedimentary sequences across the shelf, slope and the continental rise, using deep reflection seismics, sub-bottom profiler (Parasound) and swath-bathymetry (Hydrosweep) in order to derive a sedimentation model.• Mapping of the acoustic basement and its structure with deep seismic reflection methods to obtain the tectonic geometries and boundary conditions necessary to understand sediment transport and depositional processes. info:eu-repo/semantics/published